2021
DOI: 10.1021/acs.est.1c00488
|View full text |Cite
|
Sign up to set email alerts
|

Quantification and Characterization of Ti-, Ce-, and Ag-Nanoparticles in Global Surface Waters and Precipitation

Abstract: Nanoparticle (NP) emissions to the environment are increasing as a result of anthropogenic activities, prompting concerns for ecosystems and human health. In order to evaluate the risk of NPs, it is necessary to know their concentrations in various environmental compartments on regional and global scales; however, these data have remained largely elusive due to the analytical difficulties of measuring NPs in complex natural matrices. Here, we measure NP concentrations and sizes for Ti-, Ce-, and Ag-containing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 51 publications
(101 reference statements)
1
31
0
Order By: Relevance
“…The average size of TiO 2 across all sampling locations was 79.8 nm, which was larger than sizes previously reported (typically between 40 and 50 nm) elsewhere [ 41 , 53 ]. The TiO 2 PNCs were generally within a range reported across various metropoles in a study by Azimzada et al [ 34 ].…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The average size of TiO 2 across all sampling locations was 79.8 nm, which was larger than sizes previously reported (typically between 40 and 50 nm) elsewhere [ 41 , 53 ]. The TiO 2 PNCs were generally within a range reported across various metropoles in a study by Azimzada et al [ 34 ].…”
Section: Resultssupporting
confidence: 81%
“…Praetorius et al [ 32 ] and Loosli et al [ 33 ] demonstrated that SP ICP-ToF-MS improved the characterisation of suspended NMs and were able to distinguish between natural and engineered NMs by comparing elemental compositions of particles. Similarly, Azimzada et al [ 34 ] described the global abundance and composition of Ti-, Ce-, and Ag-based NMs. The performance of ICP-MS can also be improved via sector-field ICP-MS and ICP-MS/MS.…”
Section: Introductionmentioning
confidence: 99%
“… 26 However, few studies have examined the ability of spICP-TOFMS to conduct nanogeochemical analyses in aquatic systems by analyzing the composition of NNPs and natural colloids. 27 …”
Section: Introductionmentioning
confidence: 99%
“…Due to the rapid growth in their commercialization, AgNPs are likely to be released into the aquatic environment. However, there are still no fully developed analytical techniques that can specifically detect anthropogenic nanoparticles in complex matrices such as a natural environment [2,3]. Their predicted environmental concentrations (PEC) have been estimated by environmental fate models or material flow analysis in several studies (see [4] for a recent review).…”
Section: Introductionmentioning
confidence: 99%